Photodeformable Liquid Crystalline Polymers Containing Functional Additives: Toward Photomanipulatable Intelligent Soft Systems. Issue 9 (3rd June 2021) - Huang, Shuai; Huang, Yinliang; Li, Quan
Abstract : Deformable liquid crystalline polymers (LCPs) have been an attractive topic for years because of their great potential in intelligent soft systems such as artificial muscles, soft robotics, and smart optical devices. However, the application of conventional thermal‐responsive LCPs is usually limited by the low thermal conductivity of the polymer matrix and the high dependency on external heating device. In comparison, light‐controlled methods have many advantages, including being noncontact, remote in situ, and the ability to manipulate the spatial resolution of LCPs, which facilitate the development of diverse untethered and remotely manipulatable intelligent soft devices. Recently, remarkable progress has been made in the development of photodeformable LCPs by incorporation of organic or/and inorganic photoresponsive components as functional additives because the diverse functions of the incorporated components can be facilely combined with the directional shape‐morphing behaviors of LCPs in these systems via the interplay among the functional building blocks, mesomorphic phases, and polymer matrices. This review focuses on the design strategies, manufacturing methods, and working principles of photomanipulatable LCPs with incorporated photosensitive organic dyes or/and inorganic nanocomponents. Their possible applications and future developments are also briefly summarized. Abstract : By incorporating various well‐designed organic molecular dyes or/and nanocomponents into liquid crystalline polymers, it is possible to use light to achieve diverse types of photodeformation. These systems have great potentials for remote in situ and spatial resolution‐manipulatable intelligent soft robotic devices.